EFFECT OF SEASON AND SEX ON SOME PRODUCTIVE TRAITS OF PEKIN DUCK REARD INTESIVELY UNDER IRAQI CONDITIONS - & AL-Hassani, AL-Ghabban (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted at Poultry farm/Department of Animal Production/College of Agricultural Engineering Sciences/University of Baghdad, were divided into two experiments one during summer and second during winter seasons to study the effect of season and sex on productive performance of Pekin duck reared in an intensive system under harsh Iraqi conditions. A hundred fifty, one day old ducklings were used in each experiment. On 14 day of age, birds were sexed then randomly divided into nine replicates (pens) (5 replicates for females and 4 for males). Results indicated that season has significant effects on studied traits. Body weight, weight gain and food consumption were significantly ( p < 0.01 )higher in birds reared in winter than those reared in summer, whereas no significant differences existed in feed conversion ratio and mortality. Males revealed highly significant ( p< 0.01 ) in body weight and weight gain compared with females in both seasons. Study revealed that pekin duck performance were slightly effected and resisted to acute high temperature during summer. Pursuant to, it can be reared pekin duck in intensive system throughout year in Iraq.